The theme of Kristijonas Donelaitis in Johannes Bobrowski’ novel Lithuanian claviers, and in Hans-Jürgen Zierke’ short stories - Mykolaitytė, Aurelija (Literatūra, 2016)
The article deals with the reception of Donelaitis in the German literature written in the second half of 20th century. There is the focus on two authors of this time: Johannes Bobrowski and Hans-Jürgen Zierke. The novel “Lithuanian Claviers” reflects Donelaitis’ time and parallel the Nazis’ time recognising the same situation: on the one hand, hostility between different national groups, on the other hand, trying to create the atmosphere of confidence. The writer suggests that it is possible only to creative people, artists in words and music. Such person was Kristijonas Donelaitis whose life shows for nowadays people how to behave in critical situations. Bobrowski tries to revive the memory of Donelaitis who was able to defend his community and behave in his difficult time as real Christian. Zierke demonstrates other way of developing the Donelaitis’ theme. The writer describes relationship between the priest and his parishioners. There is also an emphasis on relationship with his friend, who is a priest, and wife Ana Regina. The strategy of narration is based on reconstructing the spirit of time and portraying Donelaitis. This writer went into details of Donelaitis’ life, his writings mode reminds about the historical fiction. Thus both authors reflect Donelaitis’ theme but in very different ways.